Raccomandazione : clientelism and connections in Italy - Zinn, Dorothy Louise (European anthropology in translation, 2019)
The issue of patronage-clientelism has long been of interest in the social sciences. Based on long-term ethnographic research in southern Italy, this book examines the concept and practice of raccomandazione: the omnipresent social institution of using connections to get things done. Viewing the practice both from an Indigenous perspective ' as a morally ambivalent social fact ' and considering it in light of the power relations that position southern Italy within the nesting relations of global Norths and Souths, it builds on and extends past scholarship to consider the nature of patronage in a contemporary society and its relationship to corruption.